The Socio-cultural and Political Practices of the People of the Auchi Kingdom Before the Arrival of the Nupe in Nigeria - Yakubu, Suleiman (My University, 2023)
Ancient African civilizations flourished for centuries in large expanse of land stretching from the Nile Valley to West Africa. In what is known as the Nigeran nation today was formerly made up of kingdoms and empires. One of such kingdoms was the Auchi Kingdom which was invaded by the Nupe in 1860 and they introduced some of their socio-cultural practices but the British dislodged the Nupe in 1897 by establishing British colonial rule which brought about socio-economic exploitation and also further innovations in the Auchi kingdom. Many socio-cultural and political practices of the Auchi Kingdom was abolished and the Nupe people introduced their own cultural and traditional practices after they established their imperial rule over the Auchi Kingdom. It must be said that many indigenous African traditions and socio-cultural practices dwindled away while some remained after European colonialism. Drawing from oral sources and ethnographic research in the region, the article argues that Auchi Kingdom in Nigeria had well-organized socio-cultural and political practices that was the binding force of the people before the Kingdom was overrun by the Nupe people that altered their indigenous practices in 1860 prior to the arrival of the British colonialist in 1897.
Sociokulturní a politické praktiky lidí z království Auchi před příjezdem Nupe do Nigérie
Keywords: Kingdom; Culture; Tradition; Religion; Village.; Království; kultura; tradice; náboženství; vesnice.